Mechanism in the clot formation of horseshoe crab blood during bacterial endotoxin invasion - John, Akbar; Khan Chowdhury, Ahmed Jalal; Yunus, Kamaruzzaman; Kasim, Zaleha (Asian Network for Scientific Information, 2010)
Endotoxins from gram-negative microorganisms initiates clot formation in blood when it is accidentally encountered by horseshoe crab. This property was extensively studied by various researchers as a result Limulus Amebocyte Lysate (LAL) test was established. The LAL tests in general were 3 to 300 times more sensitive than the United States Pharmacopeial (USP) rabbit pyrogen test method. It should be noted that major differences among the LAL preparations lie in the area of sensitivity. Differences, up to 100-fold, exist in the sensitivity of the various LAL preparations to the same endotoxin. It is also considerate that the Information on the molecular level interaction between horseshoe crab blood and endotoxin would provide detailed information about the clotting process. Based on the above perspective review of literature was established to elucidate the compounds involved in the clot formation in horseshoe crab blood while encountering with bacterial endotoxin. Since LAL preparation is important for its application in clinical, pharmaceutical, public health and environmental areas, this paper will also discuss some molecular level details in Lysated Amebocyte interaction in clot formation